Information supply of population concerning self-medication: state, problems and ways of optimization - Nizhenkovskaya, I. V.; Lysenko, A. Yu.; Dikukha, I. N. (Zaporozhye Medical Journal, 2013)
In the article the results of the study of self-medication process prevalence among Kiev inhabitants are presented. The research was conducted via a questionnaire. The main factors which have an influence on the development of this practice were defined as well as the sources of information about remedies for self-medication which are the most asked by inhabitants.